2020
DOI: 10.3390/fermentation6020041
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Non-Saccharomyces Yeasts Isolated from Unripened Grapes without Antifungal Treatments

Abstract: There a lot of studies including the use of non-Saccharomyces yeasts in the process of wine fermentation. The attention is focused on the first steps of fermentation. However, the processes and changes that the non-Saccharomyces yeast populations may have suffered during the different stages of grape berry ripening, caused by several environmental factors, including antifungal treatments, have not been considered in depth. In our study, we have monitored the population dynamics of non-Saccharomyces yeasts duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, from the enological and biotechnological perspectives, some yeast species are usually present during the fermentation process. After processing, three groups of non-Saccharomyces yeasts can be found in the first stages of grape must fermentation [62], during which they proliferate due to their lower tolerance to ethanol: aerobic yeasts (e.g., yeasts of genera Pichia, Rhodotorula, and Cryptococcus), yeasts with low or medium fermentation ability (e.g., genera Hanseniaspora and Metschnikowia), and yeasts with fermentative capacity (Lachancea, Zygosaccharomyces, and Torulaspora). These yeasts are then gradually replaced by the ethanol-tolerant yeast S. cerevisiae [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…However, from the enological and biotechnological perspectives, some yeast species are usually present during the fermentation process. After processing, three groups of non-Saccharomyces yeasts can be found in the first stages of grape must fermentation [62], during which they proliferate due to their lower tolerance to ethanol: aerobic yeasts (e.g., yeasts of genera Pichia, Rhodotorula, and Cryptococcus), yeasts with low or medium fermentation ability (e.g., genera Hanseniaspora and Metschnikowia), and yeasts with fermentative capacity (Lachancea, Zygosaccharomyces, and Torulaspora). These yeasts are then gradually replaced by the ethanol-tolerant yeast S. cerevisiae [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, many examinations have already been piloted to produce LGGenriched products, such as Camembert-type cheese, yoghurt, buttermilk, salad dressing, sausage, and kefir (Rodgers, 2001;Galli et al, 2019;Yousefvand et al, 2022). It has been reported that C. laurentii yeast function as a biocontrol agent against fruit pathogens (Mateo et al, 2020). In addition, this yeast was isolated from Zimbabwean traditional fermented milks (Gadaga et al, 2000).…”
Section: Introductionmentioning
confidence: 99%